Experimental device-independent certified randomness generation with an instrumental causal structure - Agresti, Iris; Poderini, Davide; Guerini, Leonardo [UNESP]; Mancusi, Michele; Carvacho, Gonzalo; Aolita, Leandro; Cavalcanti, Daniel; Chaves, Rafael; Sciarrino, Fabio (Springer Nature, 2020)
The intrinsic random nature of quantum physics offers novel tools for the generation of random numbers, a central challenge for a plethora of fields. Bell non-local correlations obtained by measurements on entangled states allow for the generation of bit strings whose randomness is guaranteed in a device-independent manner, i.e. without assumptions on the measurement and state-generation devices. Here, we generate this strong form of certified randomness on a new platform: the so-called instrumental scenario, which is central to the field of causal inference. First, we theoretically show that certified random bits, private against general quantum adversaries, can be extracted exploiting device-independent quantum instrumental-inequality violations. Then, we experimentally implement the corresponding randomness-generation protocol using entangled photons and active feed-forward of information. Moreover, we show that, for low levels of noise, our protocol offers an advantage over the simplest Bell-nonlocality protocol based on the Clauser-Horn-Shimony-Holt inequality.